PERDEBATAN MADZHAB BASHRAH DAN KUFAH DALAM PENETAPAN KAIDAH-KAIDAH NAHWU - Nurhayati, Tati; Anwar Rudi (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2023)
Nahwu as a science of the Arabic languages ​​has gone through various discussions, orientations and schools throughout its history. In the historical account of the journey of Arabic grammar science, the Bashrah and Kufah schools were two driving machines that had succeeded in delivering Arabic grammar in its golden age. However, almost in all the discussions nahwu there have been differences of opinion between the two schools, both differences in terms of approaches and methods used, thus giving birth to different ideas between the two. In this article will examine the causes and differences between Bashrah and Kufah schools in determining Nahwu’s rules. Keywords: Bahsrah Madhhab, Kufah Madhhab, Nahwu's Rule Determination